The Development of Communicative Chinese Speaking Competency by using Situation-Based Learning for Chinese Language Teaching Students - Chinnawat Sripol; Wang Weimin; Sanyakorn Srichoom (International Journal of Chinese Interdisciplinary Studies, 2024)
The research explores the effectiveness of scenario-based learning (SBL) as a method for enhancing communicative competence in the Chinese language, addressing the shortcomings of traditional methods that inadequately prepare students for real-life communication and cultural understanding. SBL offers a practical and engaging alternative that promotes active and meaningful language use. This study aimed to 1) develop Chinese speaking competency using SBL for Chinese Language Teaching students, targeting the 75/75 standard; 2) evaluate the Effectiveness Index (E.I.) of SBL; and 3) compare students' speaking abilities before and after learning with SBL. The sample included 60 students from the Chinese Teaching Program, Faculty of Education, Rajabhat Maha Sarakham University, selected via cluster random sampling. Research tools comprised 12 SBL lesson plans and a communicative Chinese speaking competency test. Statistical analysis included mean, standard deviation, and dependent t-test. The results showed 1) SBL improved students’ communicative speaking competency to 78.79/76.00, surpassing the 75/75 criteria; 2) the Effectiveness Index of SBL was 0.5569, indicating a 55.69% improvement in communication skills; 3) post-test scores were significantly higher than pre-test scores at a .05 significance level. These findings highlight SBL as an effective approach for improving Chinese language competency, promoting cultural understanding, and addressing real-life communication needs. It supports the integration of SBL in language instruction, particularly for teacher training programs, to foster active engagement and practical skill development, advancing modern language education.